Quick Response Funds and DRRM Resources in the Department of National Defense and Various Departments - Sonny N. Domingo (Philippine Institute for Development Studies (PIDS), 2014)
The study assesses the process of quick response fund (QRF) allocation, administration, and implementation under the various executive departments with cognizance of national disaster risk reduction management (DRRM) imperatives. It further touches on the inventory of the line agencies' available assets for disaster response and rehabilitation. It also looks into administration details that make up the processes of program planning, fund availment, and control within the departments of National Defense, Social Welfare, Public Works, Education, and Agriculture as well as how DRRM resources have complemented each other. Key indicators were examined and appropriation levels were analyzed to see whether the resources aid in the provision of an applicable response in the face of calamities/disasters. Trends in the QRF utilization of three departments up to fiscal year 2013 suggest the necessity of increasing the current level of standby funds for disaster response. Issues on fund control, monitoring and absorption, and sufficiency of DRRM-related assets point to entry points for structural and policy augmentations. The level of standby resources for DRR and the machinations underlying their deployment determine the timely delivery of appropriate support and services to affected communities in times of disaster.
Keywords: 330; Philippines; zero-based budgeting; disaster risk reduction management; quick response fund; calamity fund; disaster response